Continuous-flow precipitation of hydroxyapatite at 37 °C in a meso oscillatory flow reactor - Castro, Filipa (2013)
Continuous-flow precipitation of hydroxyapatite (HAp) was investigated in a meso oscillatory flow reactor (meso- OFR) and in a scaled-up meso-OFR, obtained by associating in series eight vertical meso-ORFs. Experiments were carried out under near-physiological conditions of temperature and pH, using fixed frequency ( f = 0.83 Hz) and amplitude (x0 = 4.5 mm), and varying the residence time from 0.4 to 6.7 min. It has been shown that the mean particle size and the aggregation degree of the prepared HAp particles decrease with decreasing residence time. HAp nanoparticles with a mean size (d50) of 77 nm, narrow size distribution, and uniform morphology were obtained at the lowest residence times, τ = 0.4 and 3.3 min in the meso-OFR and the scaled-up meso-OFR, respectively. These results show the capability of the meso-OFR and the scaled-up meso-OFR for continuous production of uniform HAp nanoparticles, while also confirming the possibility of OFR scale-up by in series association of individual OFRs.